Webcomic a infância do Brasil: as mediações culturais entre tecnologia e quadrinhos - Anjos, Fabio Augusto Venâncio dos (2017)
The main objective of this research is to analyze how the technology inserted in the comics causes changes and adaptations in its language and in the interaction with its readers. In order to do so, José Aguiar’s webcomic, “The Childhood of Brazil”, was chosen, for it was published completely online and presents digital resources that influence the reading and amplify the intended message through hypertexts and the mobility made possible by the responsive layout website. At first, it is considered how the technology was inserted in the production of comics and how the professionals of this activity relate to the changes caused by the uses of new tools and techniques. The following is a brief history of the career and work of José Aguiar, outlining a profile of the author and his artistic identity, manifested through his work with comics. Subsequently, the focus is on the selected webcomic, examining the chapters, their visual aspects, thematic and contexts involved, in addition to the digital resources that it makes use of. Finally, the relevance of a digital comic that deals with a rather delicate subject is approached, contemplating its legacy as art and as social criticism.